Saproxylic beetles in tropical and temperate forests - A standardized comparison of vertical stratification patterns - Weiss, Matthias; Didham, Raphael K.; Prochazka, Jiri; Schlaghamersky, Jiri; Basset, Yves; Odegaard, Frode; Tichechkin, Alexey; Schmidl, Jürgen; Floren, Andreas; Curletti, Gianfranco; Aberlenc, Henri-Pierre; Bail, Johannes; et al. (Forest Ecology and Management, 2019)
Forests are complex three-dimensional ecosystems, but little is known about the influence of vertical stratification of forest structure on biodiversity and species turnover. Saproxylic beetles make a substantial contribution to forest biodiversity and ecosystem functions such as nutrient cycling. Management measures aimed at supporting saproxylic biodiversity are becoming an integral part of sustainable forest management practices. Yet, monitoring is carried out under the assumption that saproxylic activity at ground level will be a realistic reflection of saproxylic biodiversity in the forest as a whole.
CRIS-Team WoS Importer:2019-06-28